Titanium dioxide photocatalysis for pharmaceutical wastewater treatment - Kanakaraju, Devagi; Glass, Beverley D.; Oelgemo¨ller, Michael (Springer International Publishing, 2013)
Heterogeneous photocatalysis using the semiconductor titanium dioxide (TiO2) has proven to be a promising treatment technology for water purification. The effectiveness of this oxidation technology for the destruction of pharmaceuticals has also been demonstrated in numerous studies. This review highlights recent research on TiO2 photocatalytic treatment applied to the removal of selected pharmaceuticals. The discussions are tailored based on the therapeutic drug classes as the kinetics and mechanistic aspects are compound dependent. These classes of pharmaceuticals were chosen because of their environmental prevalence and potential adverse effects. Optimal operational conditions and degradation pathways vary with different pharmaceutical compounds. The main conclusion is that the use of TiO2 photocatalysis can be considered a state-of-the-art pharmaceutical wastewater treatment methodology. Further studies are, however, required to optimize the operating conditions for maximum degradation of multiple pharmaceuticals in wastewater under realistic conditions and on an industrial scale.